The OTUD6B‐LIN28B‐MYC axis determines the proliferative state in multiple myeloma. (5th September 2022) - Paulmann, Carmen; Spallek, Ria; Karpiuk, Oleksandra; Heider, Michael; Schäffer, Isabell; Zecha, Jana; Klaeger, Susan; Walzik, Michaela; Öllinger, Rupert; Engleitner, Thomas; Wirth, Matthias; Keller, Ulrich; et al.
Abstract: Deubiquitylases (DUBs) are therapeutically amenable components of the ubiquitin machinery that stabilize substrate proteins. Their inhibition can destabilize oncoproteins that may otherwise be undruggable. Here, we screened for DUB vulnerabilities in multiple myeloma, an incurable malignancy with dependency on the ubiquitin proteasome system and identified OTUD6B as an oncogene that drives the G1/S‐transition. LIN28B, a suppressor of microRNA biogenesis, is specified as a bona fide cell cycle‐specific substrate of OTUD6B. Stabilization of LIN28B drives MYC expression at G1/S, which in turn allows for rapid S‐phase entry. Silencing OTUD6B or LIN28B inhibits multiple myeloma outgrowth in vivo and high OTUD6B expression evolves in patients that progress to symptomatic multiple myeloma and results in an adverse outcome of the disease. Thus, we link proteolytic ubiquitylation with post‐transcriptional regulation and nominate OTUD6B as a potential mediator of the MGUS‐multiple myeloma transition, a central regulator of MYC, and an actionable vulnerability in multiple myeloma and other tumors with an activated OTUD6B‐LIN28B axis. Synopsis: The deubiquitylase OTUD6B determines cell cycle progression of multiple myeloma cells by stabilizing the RNA binding protein LIN28B to attenuate microRNA‐mediated restriction of MYC at G1/S. High OTUD6B expression associates with the MGUS‐multiple myeloma progression and is an adverse outcome of multiple myeloma. OTUD6B drives proliferation of multiple myeloma cells by suppressing microRNA biogenesis via LIN28B stabilization at the G1/S cell cycle transition. OTUD6B links proteolytic ubiquitylation to mRNA biogenesis. The OTUD6B‐LIN28B axis temporally determines MYC activity in multiple myeloma. MGUS‐MM progression and adverse outcome of multiple myeloma associates with OTUD6B expression. Reducing excessive OTUD6B is a potential therapeutic target in multiple myeloma. Abstract : Deubiquitylase inhibitor screens uncover an interplay between proteolytic ubiquitylation and posttranscriptional regulation that may be targeted for multiple myeloma treatment.